2017
DOI: 10.1002/j.1681-4835.2017.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Expectations versus Reality: A Case of Internet in Nepal

Abstract: The relation between Internet and development rests on the preconditions of minimum access, quality, affordability and many more. Presenting the picture of access, quality, and affordability, we raise doubts that Nepali internet infrastructure in its present form has any contribution to economic development. The Nepali policy circle also has felt the necessity of proliferating Internet access and use. But we argue major targets of the Nepali ICT policies are detached from the reality and hence failure prone. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A recent survey in Nepal reported 51.1% of the households had access to the internet, with 44.2% of the population using it at least once a week [ 2 ]. In Kathmandu valley, about 70% of the households had access to the internet [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey in Nepal reported 51.1% of the households had access to the internet, with 44.2% of the population using it at least once a week [ 2 ]. In Kathmandu valley, about 70% of the households had access to the internet [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Regmi N in 2017, found that only 27.76% of population has access to Internet in rural Nepal but access to Television and Mobile phone was more than 95%. 17 Television and Mobile phone network can thus be used as a media to increase awareness on knowledge of COVID-19 with greater reach.…”
Section: Discussionmentioning
confidence: 99%
“…There are no official measurements or even projections. An estimate shows the energy demand of Nepali ICT during 1999–2011 was about one-third of the transportation sector (Regmi & Pandey, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Again, we could provide various arguments to support this assertion. As Regmi (2017) argues from economic perspective, the household expenditure patterns show it is difficult for the poorest 40 per cent of the households to cut-off their expenses and allocate the surplus to pay the broadband tariff. Without a significant increase in the income levels, it is likely that broadband will remain unaffordable for the majority.…”
Section: The Perennial Inequalitymentioning
confidence: 99%
See 1 more Smart Citation